Identifying EFL Learners’ Uptakes in Response to Corrective Feedback - Eka Listianing Rahayu (Masters in English Education, The Directory of Postgraduate Program,Universitas Muhammadiyah Malang, 2020)
Corrective feedback is often intended to draw learners' attention to repair linguistic forms when performing communicative activities. While researchers argue that feedback plays a role in L2 development, some teachers doubt what type of feedback is suitable for certain errors. Another issue is whether or not the given feedback is incorporated or responded by the learners. This current study focuses on two corrective feedback, namely recast and elicitation. It aims to identify which feedback elicits more uptakes from the learners. Besides, since uptakes may come in different forms, the study investigates the types of uptakes generated by learners in response to the given feedback. By involving EFL learners in a communicative task and analysing the feedback and uptake that appeared during the task, it was found that recast has elicited more uptake than elicitation. The uptake yielded includes repetition, acknowledgment, and incorporation, with repetition showing the highest frequency.